Hubungan Kecerdasan Emosional dengan Kemampuan Manajemen Stres pada Siswa Kelas XI SMKN 4 Padang Tahun Ajaran 2025/2026 - Julianti, Yeni; Linda fitria; Ananda maha putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the relationship between emotional intelligence and stress management ability among Grade XI students at SMKN 4 Padang in the 2025/2026 academic year. Students in this phase often face increased academic demands, preparation for industrial work practice, and social pressures, which may lead to elevated stress levels if not managed effectively. Emotional intelligence is considered an essential factor that can influence how students cope with such pressures. The research employed a quantitative correlational design with a simple random sampling technique, involving 70 respondents from a total population of 237 students. Data were collected using a Likert-scale questionnaire based on established theoretical indicators for both variables, and the validity and reliability of the instruments were confirmed through item analysis and Cronbach’s Alpha (0.813 for emotional intelligence and 0.854 for stress management ability). Data analysis included descriptive statistics, normality and linearity tests, and Pearson’s product-moment correlation using SPSS 24. The findings revealed a significant positive relationship between emotional intelligence and stress management ability (r = 0.608, p < 0.05), with a coefficient of determination (R²) of 36%, indicating that emotional intelligence contributes substantially to students’ ability to manage stress, while the remaining 64% is influenced by other factors. These results suggest that higher emotional intelligence enables students to regulate emotions, maintain composure, and adopt adaptive coping strategies when facing academic and social challenges. Therefore, fostering emotional intelligence could be a key approach to enhancing students’ resilience and overall well-being in the school environment.